2022
DOI: 10.1093/emph/eoac003
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell type and DNA methylation vary with reproductive status in women: possible pathways for costs of reproduction

Abstract: Background Consistent with evolutionarily-theorized costs of reproduction (CoR), reproductive history in women is associated with life expectancy and susceptibility to certain cancers, autoimmune disorders, and metabolic disease. Immunological changes originating during reproduction may help explain some of these relationships. Method ology: To explore the potential role of the immune system in female CoR, we characterized le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…The metabolic, immunological, and inflammatory profiles prevalent in high-income, Western settings, where these clocks were trained, often differ from those observed in the CLHNS and other non-Western contexts ( 51 , 52 ). More importantly, all of our follow-up samples were taken from pregnant women, whose metabolic, physiological, and immunological profiles—as well as methylomes—are quite different from the largely nonpregnant population used in the training datasets ( 53 55 ). While it is unclear to what extent the physiological, metabolic, and immunological changes that accompany pregnancy are qualitatively distinct from variation in these states among nonpregnant people ( 55 , 56 ), clocks built around these measures may be particularly sensitive to reproductive status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metabolic, immunological, and inflammatory profiles prevalent in high-income, Western settings, where these clocks were trained, often differ from those observed in the CLHNS and other non-Western contexts ( 51 , 52 ). More importantly, all of our follow-up samples were taken from pregnant women, whose metabolic, physiological, and immunological profiles—as well as methylomes—are quite different from the largely nonpregnant population used in the training datasets ( 53 55 ). While it is unclear to what extent the physiological, metabolic, and immunological changes that accompany pregnancy are qualitatively distinct from variation in these states among nonpregnant people ( 55 , 56 ), clocks built around these measures may be particularly sensitive to reproductive status.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, all of our follow-up samples were taken from pregnant women, whose metabolic, physiological, and immunological profiles—as well as methylomes—are quite different from the largely nonpregnant population used in the training datasets ( 53 55 ). While it is unclear to what extent the physiological, metabolic, and immunological changes that accompany pregnancy are qualitatively distinct from variation in these states among nonpregnant people ( 55 , 56 ), clocks built around these measures may be particularly sensitive to reproductive status. Because they are trained on chronological age, which is precisely measured and has similar meaning in all contexts, Horvath and Hannum clocks may be more robust to differences in biomarkers that vary between populations and with reproductive status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation was that our blood samples were not taken at the same time during pregnancy for each woman. This may be important because prior work has demonstrated that DNAm in general and epigenetic age specifically, and their relationship with birth outcomes, can change during pregnancy [ 36 38 ]. Nevertheless, our blood sampling occurred within a relatively narrow range of 23–41 weeks, and we adjusted all clock measures for gestational age at measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the genes affected by decreased methylation during decidualization were mainly associated with immune response regulation ( 19 , 20 ). Furthermore, DNA methylation also plays a vital role in immune cell development and maturation, which contributes to decidual immune homeostasis ( 21 23 ). Altogether, we performed a comprehensive literature review concerning the roles of TET enzymes in the microenvironment at the maternal-fetal interface during decidualization and early pregnancy.…”
Section: Introductionmentioning
confidence: 99%